Implementation of Integral Explicit Macromodels by Means of Quick-Acting Algorithms - Verlan, A.A.; Sterten, Jo (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2018)
A class of mathematical models of dynamic objects in the integral macromodels form, built on the «input-output» principle is considered. The possibility of reducing errors and increasing speed of the modeling process using quadrature formulas based on integral macromodels in the Volterra operators form (Volterra-Hammerstein) is investigated. The constructive algorithms of numerical modeling procedures are proposed using the method of dividing kernels. Розглянуто клас математичних моделей динамічних об'єктів у формі інтегральних макромоделей, що побудовані на принципі «вхід-вихід» Досліджується можливість зменшення помилок та підвищення швидкості процесу моделювання з використанням квадратурних формул на основі інтегральних макромоделей у формі операторів Вольтерра (Вольтерра-Хаммерштейн). Запропоновано конструктивні алгоритми проц